Research self-efficacy and its relationship with academic performance in postgraduate students of Tehran University of Medical Sciences in 2016 - Amir Tiyuri; Behzad Saberi; Mohammadreza Miri; Ehsan Shahrestanaki; Beyram Bibi Bayat; Hamid Salehiniya (Wolters Kluwer Medknow Publications, 2018)
Background: Research self-efficacy is one of the main factors influencing the successful conduction of research and following it in students. This study was performed with the aim of determining the research self-efficacy and its relationship with academic performance in postgraduate students of Tehran University of Medical Sciences (TUMS) in 2016. Materials and Methods: This cross-sectional study was performed on 320 postgraduate students of TUMS in 2016. Proportional stratified sampling was done with simple random sampling from each school. The data were gathered with Phillips and Russell's research self-efficacy questionnaire, demographic questions, and grade point average (GPA) and were analyzed with independent t-tests, ANOVA, Pearson's correlation, and multiple linear regressions in SPSS 18. Results: Out of 320 students participating in this study, 152 patients (47.5%) were male and 168 (52.5%) were female with the mean age of 27.83 ± 4.3 years. The mean of research self-efficacy score was 186.18 ± 59.5 which was significant depended on college degrees and was significantly higher in doctorate students (P = 0.0001). However, no significant difference was seen in research self-efficacy score of students due to gender (P = 0.754) and school (P = 0.364). There was a significant direct relationship between students' GPA and research self-efficacy score (r = 0.393, P = 0.0001). Conclusions: Results of this study showed that the research self-efficacy score of TUMS postgraduate students is at an acceptable level, except the quantitative and computer skills that need appropriate educational interventions. As a direct and significant relationship existed between research self-efficacy score and student's academic performance, improving the research self-efficacy will also increase students' academic performance.